Hubungan Pengetahuan dan Dukungan Keluarga dengan Perilaku Penyalahgunaan Napza di Kelas IIA Lembaga Pemasyarakatan Jambi - Nel Efni (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The causes of drug abuse are complex due to the interaction of various factors, including individual factors such great curiosity to try and unknowingly or think long about the consequences later in life, environmental factors such as family problems or a broken home or social environment / community one even all members become abusers drug. This research is a quantitative research using Cross sectional design. The population in this study is the victim of drug abuse which amounted to 545 people and a total sample of 40 respondents using simple random sampling technique and the data were analyzed using univariate and bivariate by using the chi-square test. There is The relationship of knowledge and family support to the behavior of drug abuse in class IIA prison  Jambi. Expected to be used as inputs in the preparation of the program increased knowledge about the dangers of drugs.